Diversification of rice (Oryza sativa) based cropping system for higher productivity and income enhancement in the middle Indo-Gangetic Plains of eastern India - SHIVANI; KUMAR, SANJEEV; SHUBHA, KUMARI; SAURABH, KIRTI; KUMAR, ABHISHEK; MANIBHUSHAN; UPADHYAYA, A; DAS, ANUP (The Indian Journal of Agricultural Sciences, 2025)
A field experiment was conducted for three consecutive years during 2019–20, 2020–21 and 2021–22 at ICAR-Research Complex for Eastern Region, Patna, Bihar to assess the best and profitable rice (Oryza sativa L.) based cropping system through crop diversification for sustainable agriculture. Diversification of wheat (Triticum aestivum L.) with rabi vegetables and inclusion of green gram (Vigna radiata L.) during summer season in rice-wheat cropping system was studied with rice cultivars of different duration. The rice-cauliflower (Brassica oleracea var. botrytis)-spinach (Spinacia oleracea L.)-green gram system recorded the highest system productivity with a rice equivalent yield of 34.26 t/ha, followed by the rice-broccoli (Brassica oleracea var. italica)-spring onion (Allium fistulosum)-green gram system (32.47 t/ha) which were more than double as compared to rice-wheat-green gram system (12.29 t/ha). Land use efficiency was recorded maximum in rice-tomato (Solanum lycopersicum)-green gram system (95.34%) and minimum in rice-garden pea (Pisum sativum L.)-green gram system (82.19%). Growing shorter duration rice cultivar (Swarna Shreya) in the cropping systems significantly enhanced the system productivity, system production efficiency and income as compared to longer duration rice variety in different cropping systems. Diversification of wheat with rabi vegetables enhanced the gross return, net return and benefit cost ratio irrespective of rice duration. The cropping intensity was also increased by diversifying wheat with cauliflower and broccoli grown after short duration rice (400%), as it provided an opportunity to grow a short span crop in the rabi season itself before sowing of green gram during summer season.